Pengaruh Teknik Relaksasi Napas Dalam terhadap Penurunan Persepsi Nyeri pada Lansia dengan Artritis Reumatoid - Sartika, Dina Dewi; Setyoadi; Widastra, Ni Made (Jurnal Keperawatan Soedirman, 2009)
Research was done to provide that deep relaxation technique can decrease pain perception for old man with Arthritis Rheumatoid. The aim of this research was to know the stage of pain perception before and after give relaxation technique, to know differentiation and analysis the result of differentiation. This research is quasi experiment with Time Series Design method. Using 10 respondents, that was found with accidental sampling. Independent variable was influence of deep relaxation and dependent variable was decrease pain perception for old man with Arthritis Rheumatoid. The result shows that deep relaxation technique was significantly influence of pain perception Arthritis Rheumatoid patients. Wilcoxon Signed Rank Test show at ? =0.05 (p = 0.005 with confidence interval at 95 %,). Based on these facts above, relaxation method is useful for old man to solve pain problem and for nurses can apply deep relaxation technique to decrease pain perception for old man with Arthritis Rheumatoid as independent nursing intervention.